EMPOWERING NATURAL RESOURCES AND HUMAN RESOURCES IN THE SEBUMI PROJECT TO PREVENT COVID-19 - Desmawati, Desmawati; Agustina, Agustina; Samaria, Dora; Ritanti, Ritanti; Ayu Marcelina, Lina; Sucika, Dara; Aprilia, Farah; Shahidda, Nadia; Nur’aeni Wisudawati, Sulistya; Dwi Suciantie, Pramesti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Although Covid-19 has been reported as zero, however, people are always vigilant in dealing with Covid-19. Empower of community is needed to prevent and adapt to Covid-19. These natural and community service activities aim to increase prevention efforts of COVID-19 with clean water source projects. The methods used are socialization, or refreshing content related to COVID-19 to cadres and as well as the residents, then advocacy is carried out on RT, RW, and village heads regarding the COVID-19 prevention program, The output of this program is the availability of clean water source In Baduy as a facility for hand washing, cooking, etc., The results of the study reported that there was an increase in enthusiasm for carrying out a clean healthy lifestyle after socialization to prevent covid-19 as much as 81.8% (good) and the rest were very good, as well as the establishment of drilled wells as a source of clean water. Qualitatively, the results of this humanitarian project created an atmosphere of sharing among residents with clean water distributed to residents. This is very helpful for residents as an effort to prevent the spread of Covid-19 as a whole. In addition, involving people who influence the community such as religious leaders and influential citizens is also very helpful in supporting each other and reminding each other to always implement health prevention of COVID-19